Ecopreneurship in Malaysia. - Kamarulzaman, Nitty Hirawaty; Mohd Nawi, Nolila (Universiti Putra Malaysia Press, 2012)
Entrepreneur can be defined as ‘a person who have ideas of new business opportunities and creates enterprises from scratch and normally have limited resources and with an abundance of risks’ (Schaper, 2002). Entrepreneurs may act as catalysts for change and advancement in both economic and environmental perspectives (Volery, 2002; Anderson, 1998; Isaak, 2002; Krueger, 1998; Pastakia, 2002). The belief that entrepreneurs are not environmentally aware, or do not care to be, is quickly becoming outdated (Porter and van der Linde 1995; Anderson 1998), as currently there is an increasing number of green entrepreneurs, known as ecopreneurs. According to Kirkwood and Walton (2010), the growth in eco-friendly entrepreneurs may be partially due to increasing market opportunities for sustainable products and services. Customers are becoming increasingly environmentally conscious (Laroche et al., 2001). Many customers are losing confidence in larger corporations and have expectations of companies to exhibit more social and environmental responsibility (Webb et al., 2008). Schumpeter (1934) argued that the innovations made by entrepreneurs are the strategic factors in economic development and the central factors in the trade cycle. Further, there is convincing evidence in Volery (2002) that over the past decades the natural environment growth does not go hand in hand with the preservation of nature. Increasing pollution levels, loss of biodiversity, land degradation, and climate change are only a few examples of this scenario. This suggests that an increasing need for environmental responsibility in ecopreneurship is crucial (Volery, 2002). Entrepreneurship and sustainability are considered to be the emergent paradigms of the late 20th century (Anderson, 1998) thus, we need to respond and move towards that paradigms so that our entrepreneurs can be more competitive.